Un conservatoire des plâtres antiques, 1 - Élisabeth Le Breton (In Situ)
It’s on the ruins of a vast collection of plaster casts of classical antiquity sculpture demystified since 1968 that is standing, since 2001, the gypsothèque (mouldings library) of the Louvre Museum. Nearly two decades of restoration and research made it possible today to rekindle the memory of some part of these 5,500 works sheltered under the high vaulted ceilings of the Petite Écurie du roi, the King’s Small Stables at Versailles.Indeed, the finding of specific “identity cards” enabled the creation of a historical timeline of the appropriation of these models from the Antiquity in Paris from the 16th to the 20th century and thereby offers a better understanding of the intent behind those selections of works. The first “plastres”, all Roman, substitutes similar to the marbles rediscovered during the Renaissance period but that were not allowed to be removed from the Papal States, were present in the royal collections. They were in great numbers in the King’s Room of Antiques, then, from 1666, they were gradually present in the rooms of the “Académie royale de peinture et de sculpture” (“Royal Academy of painting and sculpture”) next-door. A the end of the 18th century, a complete change in the situation occurred; plasters were removed from the private and enclosed places where they were kept, to be henceforth, called upon to play a major role in the Public education. From 1791 onwards, the models circulated and in 1794, a moulding workshop was founded in the Louvre. The democratization of art was at the core of revolutionary initiatives and led to the transfer of the Louvre’s collections to the left bank of the Seine, for a different fate, in the “École royale et spéciale des beaux-arts” (the “Royal and special school of fine arts”), that will undertaking a much more ambitious project, from 1816 onwards, in the “Nouvelle École royale et spéciale des beaux-arts” (“New Royal and Special School of Fine Arts”) in Paris.